Domínio ortográfico da língua portuguesa no contexto bilíngue Ticuna /Português na aldeia Filadélfia em Benjamin Constant – Alto Solimões- AM. - Oliveira, Carlos Alberto Silva de (2017)
The mastery of the Portuguese Language spelling is a complex path that the teacher and the student walk in all phases of school and personal life. Seeking to exercise this linguistic competence is one of the fundamental conditions for its intellectual and educational growth. Thus, this work aimed to investigate and analyze the forms of representation and appropriation of the Portuguese Language spelling, with emphasis on spelling deviations or alterations by Ticuna students in the indigenous high school named Professor Gildo Sampaio Megatanücü, located in Philadelphia Village, in Benjamin Constant city, in the micro-region of Alto Solimões – Amazonas state. The analysis was carried out from written activities, dictations of words, phrases, texts, productions of spontaneous texts and exercises of verification on the stress rules and signs, applied during the regular hours of school. The study on the spelling of the students was guided by the studies of Zorzi (1998), Cagliari (1997), with great contribution of Soares (1995) on the issue of Ticuna Language Phonology. Concerning to the study being carried out with indigenous populations whose mother tongue is Ticuna, we analyzed the accuracy of spelling and its relation with the deviations motivated by the complexity itself of the spelling system and with those motivated by the linguistic contact. Among the main aspects of the results, we can highlight a greater tendency for spelling deviations related to multiple representations (31.1%), orality support (21.9%) and deviations due to absence, displacement and stress signs exchanges (14%), what demonstrates a greater difficulty at these 3 (three) deviations mentioned from the 3,623 (three thousand, six hundred and twenty-three) classified ones. Likewise, we analyzed the deviations motivated by the linguistic contact: the Spelling Hybridism, whose changes were marked by the formation of words with the structure of both languages (Portuguese/Ticuna or Portuguese/Spanish). KEYWORDS: Ticuna; Spelling; Portuguese Language